PENERAPAN STRATEGI PROMOSI PADA UMKM HOME LAUNDRY - Sonata, Vivi; Yuwono, Wisnu (Lembaga Riset dan Inovasi Kreyat Center, 2023)
Home Laundry is an SME that operates in the clothing laundry service sector. SME Home Laundry offers clothes washing, dry cleaning, and ironing services, clothes, and washing dolls, shoes, carpets, and others. The income earned by SMEs is considered unstable, therefore this service activity is carried out to help SMEs solve these problems. The data collection methods used in this activity were observation and interviews. This activity produces a digital marketing strategy for SMEs to implement through social media Instagram and the advice that can be given to SME is that SMEs can take advantage of advances in digital technology to carry out promotions and attract customer attention which has a good impact on the development of SME businesses.